Analysis of supply system models for planning construction project logistics - Sobotka, Anna; Czarnigowska, Agata (Journal of Civil Engineering and Management, 2005)
The paper discusses a number of construction project logistics problems, with focus on supply systems, and presents the results of recent survey of Polish contractors’ supply routines. On the basis of the survey, patterns of development of logistic systems have been described. The enclosed results of cost simulations indicate that outsourcing supply logistic processes, considering the current state of Polish construction market, may reduce costs. The paper emphasises that creating logistic guidelines of a project at its early stages of planning and then a design of integrated logistic service to the project may help find ways of making a construction project more effective. Statybos projektų logistikos planavimui taikomų tiekimo sistemos modelių analizė Santrauka. Apžvelgti Lenkijos rangovų tiekimo procesai, nagrinėjamos statybos projektų logistikos problemos. Aprašomi logistikos sistemų vystymo variantai. Tiekimo procesų logistikos modeliavimas leidžia sumažinti išlaidas. Parodyta, kad ankstyvosiose projektavimo stadijose tikslinga suformuluoti svarbiausius logistikos principus ir kurti integruotą logistinio aptarnavimo centrą. Šios priemonės leidžia rasti papildomų būdų statybos projektų efektyvumui didinti. Raktiniai žodžiai: logistika, išlaidos medžiagoms įsigyti, statybos projektas, tiekimo sistema, logistikos centras. First Published Online: 14 Oct 2010